2015
DOI: 10.1186/s13750-015-0050-7
|View full text |Cite
|
Sign up to set email alerts
|

What is the impact of active management on biodiversity in boreal and temperate forests set aside for conservation or restoration? A systematic map

Abstract: Background:The biodiversity of forests set aside from forestry is often considered best preserved by non-intervention. In many protected forests, however, remaining biodiversity values are legacies of past disturbances, e.g. recurring fires, grazing or small-scale felling. These forests may need active management to keep the characteristics that were the reason for setting them aside. Such management can be particularly relevant where lost ecological values need to be restored. In this review, we identified st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 65 publications
0
45
0
Order By: Relevance
“…[48] or a more complex interactive world map which also enables the reader to select studies from sub-topics of interest and access study meta-data e.g. [50,51]. This can easily be undertaken using online tools, such as Google Maps, if all study lines in an Excel database have latitude and longitude associated with them.…”
Section: Visualising the Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…[48] or a more complex interactive world map which also enables the reader to select studies from sub-topics of interest and access study meta-data e.g. [50,51]. This can easily be undertaken using online tools, such as Google Maps, if all study lines in an Excel database have latitude and longitude associated with them.…”
Section: Visualising the Findingsmentioning
confidence: 99%
“…Systematic maps may be of potential interest to a wide range of stakeholders, including policy makers, practitioners, non-governmental organisations, levy boards, scientists and research funding bodies e.g. [26,[45][46][47][48][49][50][51][52].…”
Section: Stagementioning
confidence: 99%
“…At the request of Swedish stakeholders, who wished to get an overview of the scientific support for various ways of managing protected forests, we recently published a systematic map focused on the effects of active management on biodiversity in forests set aside for conservation or restoration [19]. A systematic map does not synthesise reported results but rather provides a summary of the evidence base, and it can therefore be seen as a first step towards more complete reviews of selected subtopics.…”
Section: Identification Of Review Topicmentioning
confidence: 99%
“…Most of the evidence on which this systematic review will be based is included in the recently completed systematic map of biodiversity impacts of active management in forest set-asides [19]. Of the 812 studies in the map, 149 reported on how plants or invertebrates were affected by manipulation of grazing or browsing.…”
Section: Selection Of Studies Identified In the Systematic Mapmentioning
confidence: 99%
“…Today, unlike in the past, the renewal process is usually impossible especially in the areas under strict protection favourable for natural succession with strong fragmentation loss of continuity and lack of essential disturbances, for example, fires. In this particular situation the only solution for survival for many species and habitats in europe is to reintroduce the active conservation methods (Bernes et al 2015;Sebek et al 2015).…”
mentioning
confidence: 99%